Evaluating User Experience and Enjoyment with E-Government Portal in Libyan Higher Education - Asma M Abdaljalil; Anwar Alhenshiri (Libyan Journal of Medical and Applied Sciences, 2025)
E-government portals have become vital tools for modernizing public services, particularly in higher education. This pioneer study evaluates the usability and user enjoyment of the Libyan Ministry of Higher Education’s e-government portal, focusing on key dimensions such as effectiveness, efficiency, and user satisfaction. Despite its role in streamlining administrative processes, users frequently encounter challenges, including unclear instructions, restrictive data update processes, and insufficient feedback mechanisms. Findings indicate that while the portal performs well in efficiency and effectiveness, user enjoyment remains a critical area for improvement. Strong correlations between usability factors suggest that addressing identified issues—such as enhancing interface design, improving task guidance, and implementing real-time feedback mechanisms—can significantly enhance user experience. This research provides actionable recommendations to optimize e-government portals, ultimately supporting the digital transformation of Libya’s higher education sector.